The Relationship Between Followership Styles And Employees’ Job Performance In A Selected Public University - Adriana Kamalia, Abd Shukor (Universiti Malaysia Sarawak (UNIMAS), 2020)
The aim of this study is to analyze the relationship between followership styles and employees’ job performance in a selected public university in Peninsular Malaysia. This study applies the Kelley’s Followership Model in assessing all employees’ followership style. Overall, 108 non- academic staff from the selected university has participated in the research. A quantitative approach was used to gather data from respondents using questionnaires which comprises of demographic information, the Kelley’s Followership Questionnaire (Kelley, 1992) and the Individual Work Performance Questionnaire 1.0 (Koopmans, 2014). IBM SPSS was used in conducting Spearman’s Correlation in order to analyze all data collected. The results shows that exemplary and alienated followership styles have a significant relationship with employees’ job performance while passive, pragmatic and conformist followership style have no significant relationship with employees’ job performance. These findings have contributed to the literature of followership and job performance in Malaysia in which it will provide as a support for further researches.